Pengaruh Kompensasi, Loyalitas Karyawan, dan Kepuasan Kerja Terhadap Keterlibatan Kerja Karyawan pada PT Indonesia Steel Tube Works Semarang - Rachma Zanuar; Mohammad Fauzan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of the study was to analyze and explain the effect of (1) compensation on employee work engagement, (2) employee loyalty on work engagement, (3) job satisfaction on employee work engagement at PT Indonesia Steel Tube Works Semarang. This study used a sample of 108 company employees. Data collection uses a questionnaire through a google form sent to employees. The collected data is then processed with the help of the SPSS application. The test models used are validity and reliability tests, F tests and determination coefficient tests and hypothesis tests. The findings of the study show that: (1) compensation has a positive effect on employee work engagement, (2) employee loyalty has a positive effect on employee work engagement, (3) job satisfaction has a positive effect on work engagement in employees of PT Indonesia Steel Tube Works Semarang.